2015
DOI: 10.5573/jsts.2015.15.5.526
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Instability Mechanism under Simultaneous Positive Gate and Drain Bias Stress in Self-Aligned Top-Gate Amorphous Indium-Zinc-Oxide Thin-Film Transistors

Abstract: Abstract-We

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…), and that the amount of ionization is greater than the amount of electron trapping. Under the PBS, the drain current reached 300 µA which induces sufficient joule heating to raise the local temperature of the a-IGZO channel, inducing the activation of shallow donor states (oxygen vacancies) [29][30][31]. Therefore, while electron trapping and oxygen vacancy ionization induce positive and negative V th shifts, respectively, the oxygen vacancy ionization was more dominant than electron trapping under the PBS condition with the high drain current, resulting in a negative V th shift [32,33].…”
Section: Resultsmentioning
confidence: 99%
“…), and that the amount of ionization is greater than the amount of electron trapping. Under the PBS, the drain current reached 300 µA which induces sufficient joule heating to raise the local temperature of the a-IGZO channel, inducing the activation of shallow donor states (oxygen vacancies) [29][30][31]. Therefore, while electron trapping and oxygen vacancy ionization induce positive and negative V th shifts, respectively, the oxygen vacancy ionization was more dominant than electron trapping under the PBS condition with the high drain current, resulting in a negative V th shift [32,33].…”
Section: Resultsmentioning
confidence: 99%
“…For the reliable incorporation of a-IGZO TFTs into the driving circuits for display application, it is crucial to understand the degradation mechanisms of the device under bias stresses. Many research groups have reported stress-induced instability characteristics [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Most of these studies have focused on the verification of degradation mechanisms, such as charge trapping, hole trapping, and donor-state creation.…”
Section: Introductionmentioning
confidence: 99%
“…It is necessary to predict the circuit operation in alternating current (AC) driving conditions through simulations that reflect analysis results. Until now, there has been much research on direct current (DC) stress [9][10][11][12][13][14][15][16][17], even though most circuits are driven in AC conditions. Hence, it is very important to analyze the instability characteristics of IGZO devices and circuits in various AC conditions so that compact modeling can be drawn for the reliability-aware SPICE (Simulation Program with Integrated Circuit Emphasis) simulation.…”
Section: Introductionmentioning
confidence: 99%